Mass casualty incident preparedness and response: A desk review of the Code Orange Plan and Assessment of Healthcare Workers’ Knowledge, Attitudes, and Practices in a Lebanese Tertiary Government Hospital - Linda Abou-Abbas; Rima Kashash; Mustapha Khalife; Mohamad Shafic Ramadan (PLoS ONE, 2026)
Background Effective preparedness and response to mass casualty incidents (MCI) are essential for hospital safety, operational efficiency, and the delivery of timely, high-quality patient care during emergencies. This study assessed a tertiary government hospital in Lebanon’s Code Orange plan by reviewing documentation for alignment with international guidelines and evaluating staff knowledge, attitudes, and practices (KAP) regarding MCI preparedness. Methods Documents reviewed at Rafik Hariri University Hospital (RHUH) included the current Code Orange plan, relevant policies, and international guidelines. A comprehensive evaluation framework was used, focusing on preparedness, incident command systems, communication, and management. A comparison with established standards was conducted to identify gaps. Complementing this, a cross-sectional study was conducted using a convenient sample of medical and non-medical healthcare workers to evaluate their KAP regarding MCI preparedness. Results The desk review of the RHUH Code Orange plan identified both strengths and significant gaps in MCI preparedness. While the plan defines staff roles and resources for emergency response, it lacks detailed procedures for activation strategies, surge capacity, continuity of essential services, and triage processes. Additionally, post-event recovery protocols are insufficient or absent, and the importance of regular drills is not adequately emphasized. The KAP study revealed significant differences between medical and non-medical staff in terms of MCI knowledge, involvement, and training engagement, with medical staff reporting higher levels of familiarity and desire for participation. Conclusion The findings underscore the need to bridge knowledge and engagement gaps between medical and non-medical staff to enhance MCI response. Key actions include interdisciplinary training to build coordination, clear communication protocols to streamline information flow, and routine drills with defined roles to strengthen preparedness. Additionally, implementing performance monitoring during drills and real MCIs, along with conducting regular evaluations, will allow for continuous refinement of response strategies.